2007
DOI: 10.1001/archinte.167.13.1393
|View full text |Cite
|
Sign up to set email alerts
|

Health Care–Associated Pneumonia Requiring Hospital Admission

Abstract: Background: Health care-associated pneumonia (HCAP) has been proposed as a new category of respiratory infection. However, limited data exist to validate this entity. We aimed to ascertain the epidemiology, causative organisms, antibiotic susceptibilities, and outcomes of and empirical antibiotic therapy for HCAP requiring hospitalization. Methods: Observational analysis of a prospective cohort of nonseverely immunosuppressed hospitalized adults with pneumonia. Patients who had recent contact with the health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(126 citation statements)
references
References 26 publications
12
104
4
2
Order By: Relevance
“…Only 16.3% of the cohort had a CURB-65 score of Ͼ2, a cutoff that would be associated with an anticipated mortality of greater than 3% (11). Previous studies have suggested an increased mortality rate with HCAP compared to CAP in univariate analysis (12,15,17,23). In our study, the high mortality with HCAP was likely due to more comorbidities and higher admission disease severity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Only 16.3% of the cohort had a CURB-65 score of Ͼ2, a cutoff that would be associated with an anticipated mortality of greater than 3% (11). Previous studies have suggested an increased mortality rate with HCAP compared to CAP in univariate analysis (12,15,17,23). In our study, the high mortality with HCAP was likely due to more comorbidities and higher admission disease severity.…”
Section: Discussionmentioning
confidence: 58%
“…The previously mentioned United States-based studies included only patients with a bacterial pathogen isolated (12)(13)(14). These studies do not reflect the true spectrum of CAP and HCAP, since prospective studies have defined a specific microbiologic etiology only in 16% to 63.8% of CAP patients and 21% to 67.5% of those with HCAP (15)(16)(17)(18)(19). Moreover, pathogens such as S. aureus and P. aeruginosa may be more easily grown from sputum specimens compared to S. pneumoniae (2).…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics that meet definitions for HCAP include residence in a nursing home or extended-care facility, recent hospitalization, recent antimicrobial exposure, the need for long-term hemodialysis, home infusion therapy or home wound care, and underlying immunosuppression. While these risk factors have been corroborated in other geographic settings (687,(705)(706)(707)(708), the prevalence of potentially resistant pathogens causing HCAP in these regions varies considerably (709).…”
Section: Epidemiologymentioning
confidence: 95%
“…Patients with MRSA pneumonia incur an increased cost of care compared to patients with MSSA pneumonia (683). At present, then, S. aureus remains a well-known pathogen in both CAP and HCAP presentations, and modern isolates are a mix of methicillin-susceptible and methicillin-resistant strains (684)(685)(686)(687).…”
Section: Epidemiologymentioning
confidence: 99%
“…Cases were then manually reviewed and included only if they met study criteria for confirmed pneumonia. The case definition for pneumonia was based closely upon other studies in health care-associated pneumonia (15)(16)(17)(18): radiographic evidence of infiltrate or cavitation and the presence of two or more of the following clinical signs or symptoms: (i) temperature less than 36.0°C or greater than 38.0°C, (ii) respiratory rate greater than 20, (iii) cough, (iv) hypoxia as evidenced by oxygen saturation less than 90% on room air, (v) increased sputum production, or (vi) a white blood cell count less than 4,000/mm 3 or greater than 10,000/mm 3 . Patients with confirmed pneumonia who had a nasal swab MRSA PCR test and from whom a culture specimen also was obtained were included in the study.…”
Section: Methodsmentioning
confidence: 99%